A meta-analysis of resting-state fMRI in postherpetic neuralgia using AES-SDM - Wu, Guanzuan; Luo, Yurou; Guo, Danling; Lv, Sangying; Yang, Jianfeng (Frontiers in Neuroscience, 2025)
BackgroundResting-state fMRI (rs-fMRI) has revealed a range of neural activity patterns in patients with postherpetic neuralgia (PHN). However, inconsistencies in study design have led to conflicting findings in previous research studies. This meta-analysis used the anisotropic effect size-signed differential mapping (AES-SDM) approach to evaluate rs-fMRI studies on PHN and to provide more robust insights into the brain networks involved in processing PHN pain.Materials and methodsA systematic search of PubMed, Embase, Web of Science, and the Cochrane Database was performed for rs-fMRI studies comparing PHN patients with healthy controls, up until 1 November 2024. The AES-SDM approach was then employed to meta-analyze the abnormal brain activity patterns observed in PHN patients.ResultsA total of eight articles were included in the analysis comprising 148 patients with PHN and 179 healthy controls. The meta-analysis found that patients with PHN exhibited increased activity in the right middle temporal gyrus (MTG.R), right precuneus (PCUN.R), and right superior frontal gyrus, orbital part (ORBsup.R). In contrast, a reduction in functional activity was observed in the left superior frontal gyrus, medial (SFGmed.L), left calcarine fissure/surrounding cortex (CAL.L), right precentral gyrus (PreCG.R), and right inferior temporal gyrus (ITG.R). Sensitivity analysis revealed that all of these regions exhibited high reproducibility, and no significant publication bias was identified.ConclusionThis meta-analysis reveals altered specific brain activity in PHN patients, providing a foundation for targeted treatments that address both sensory and affective aspects of chronic pain.Systematic review registrationPROSPERO, registration no. CRD42024614718; https://www.crd.york.ac.uk/PROSPERO/view/CRD42024614718.